Comparison of horned, polled Bali cattle and Banteng based on microsatellite markers - DAGONG, MUHAMMAD IHSAN ANDI; AGUNG, PASKAH PARTOGI; SAPUTRA, FERDY; ZULKHARNAIM, ZULKHARNAIM; SAID, SYAHRUDDIN; KAIIN, EKAYANTI MULYAWATI; ZEIN, MOCH SYAMSUL ARIFIN (The Indian Journal of Animal Sciences, 2023)
Bali cattle (Bos javanicus) are domesticated cattle from Banteng. Bali cattle have unique characteristics that is the white sock. In the Maiwa breeding center, Enrekang district, South Sulawesi Province, polled Bali cattle are being kept in large quantities, both male and female. The microsatellites are widely used in the study of population genetics and quantitative trait locus. Therefore, the study aims to observe genetic diversity and determine whether microsatellites can distinguish horned Bali cattle, polled Bali cattle, and Banteng as their wild relatives. DNA was isolated from blood samples of 57 Bali cattle from two different populations: horned Bali (n=20) from Nusa Penida Island Bali province, polled Bali cattle (n=37) from Maiwa Breeding Center, South Sulawesi province, and 20 samples of Banteng from Ragunan Zoo (n=10), Jakarta Province and Surabaya Zoo (n=10), East Java Province. Genotyping was done using 11 microsatellite markers. The size of each microsatellite marker was determined using GeneMapper version 5.0. The observed heterozygosity value (Ho), expected heterozygosity value (He), the heterozygote deficit within the breed (Fis), gene flow (Nm), Hardy-Weinberg equilibrium (HW), and allele frequency were performed using CERVUS version 3.0.7 program. The FSTAT 2.9.4 was performed to obtain Fis value from two different populations.Similarly, bayesian clustering assignments were analyzed using STRUCTURE version 2.2. The polymorphism information content of eleven microsatellite markers ranged from 0.390-0.879. Moreover, we found Fis values of all markers which depicted that there is no inbreeding in horned and polled Bali cattle populations. We also found that polled Bali cattle have more private alleles than horned Bali cattle. Using Bayesian analysis, we found different genetic structures between polled Bali and horned Bali cattle with the K optimal at K=3. Findings indicated that ILST6 allele 288, TGLA53 allele 132, and TGLA227 allele 70 can be considered as the private allele to differentiate between the horned, polled Bali cattle and Banteng.